The Cost-Production Duality Approach To The Measurement Of Labour Productivity: A Dynamic Tool For Effective Human Resource Management - G. Van Zyl (SA Journal of Human Resource Management, 2004)
Positive real increases in the prices of inputs, as the result of an inefficient level of productivity, can no longer be accepted in competitive markets. The survival and more specifically the competitiveness of businesses and industries is critically dependent on a higher level of cost efficiency and in particular a more productive input base. The aim of the paper is to present the methodology, structure and results of a new dual cost-production instrument where changes in the level of labour productivity can be measured. A scientific derived and well-tested instrument is developed. This instrument should enable human resource managers to monitor productivity changes more effectively and make timely decisions on ways and means that could improve the productivity of labour. Opsomming Positiewe reële toenames in die pryse van insette as die resultaat van ’n oneffektiewe vlak van produktiwiteit kan nie langer in mededingende markte geduld word nie. Die oorlewing en meer spesifiek die mededingendheid van ondernemings en industrieë is krities afhanklik van ’n hoër vlak van koste-doelmatigheid en in die besonder van ’n meer produktiewe inset basis. Die doel van die publikasie is om die metodiek, struktuur en resultate van ’n nuwe gelyktydige koste-produksie instrument bekend te stel waarmee veranderinge in die vlak van arbeidsproduktiwiteit gemeet kan word. ’n Wetenskaplik-afgeleide en getoetste instrument is ontwikkel. Diè instrument behoort personeelpraktisyns in staat te stel om produktiwiteitsveranderinge meer effektief te kan monitor en gevolglik tydige besluite te kan neem oor wyses waarop arbeidsproduktiwiteit verbeter kan word.